Preparation and Characterization of Electrospun Polysaccharide FucoPol-Based Nanofiber Systems - Vázquez-González, Yuliana (2022)
code 319RT0576 RTI-2018-097249-B-C21 reference number 836884 UIDP/04378/2020 UIDB/04378/2020 LA/P/0140/2020